From Data to Records: Preserving the Geographic Information System of the City of Vancouver - Dingwall, Glenn; Marciano, Richard; Moore, Reagan; Peters McLellan, Evelyn (Archivaria, 2007)
VanMap is a geographic information system used by the municipal government of the City of Vancouver, British Columbia. It provides city staff access to a wide variety of continuously changing spatial information about the city, drawn from internal and external sources, which is used in support of both formal and informal business processes. In the first part of the article, the authors address issues related to the long-term preservation of VanMap encountered in the course of the InterPARES 2 case study conducted in 2004–2005. VanMap is examined within the context of InterPARES concepts of the record in dynamic and interactive environments, and subsequent implications in terms of establishing the essential elements of the system that must be preserved and how to relate the preserved system to the activities it supported are discussed. The second part of the article explores the how the Storage Resource Broker data-grid technology developed at the San Diego Supercomputer Center might be used as a component in the overall preservation strategy. This technology would support maintaining the integrity and authenticity of the preserved system, and contribute to its infrastructure independence through features such as persistent namespaces. RÉSUMÉ VanMap est un système d’information géographique utilisé par le gouvernement municipal de la ville de Vancouver, en Colombie-Britannique. Il permet au personnel municipal en quête de données sur la ville, d’accéder à une grande variété d’information spatiale en constante évolution, puisée de sources internes et externes, qui servent à appuyer les procédés administratifs officiels et non-officiels. Dans la première partie de cet article, les auteurs examinent des questions relatives à la préservation à long-terme de VanMap, questions soulevées lors de l’étude de cas faite dans le cadre du projet InterPARES 2 en 2004-2005. Ils examinent VanMap dans le contexte des concepts élaborés par InterPARES sur les documents dans des milieux dynamiques et interactifs, puis ils se penchent sur les questions qui en découlent, à savoir comment établir les éléments essentiels du système qui doivent être préservés, et comment lier le système préservé aux activités qu’il supportait. La deuxième partie de l’article explore comment la technologie Storage Resource Broker, développée au San Diego Supercomputer Center, pourrait servir comme composante d’une stratégie de préservation complète. Cette technologie pourrait appuyer le maintien de l’intégrité et de l’authenticité du système préservé, et contribuer à l’indépendance de son infrastructure grâce à des caractéristiques comme l’espace de nommage fixe.